Flight path analysis in sounding rocket “Libertador I” with computational simulation on three degrees of freedom - Murcia, J. (2014)
This paper presents obtained results from computer simulations in order to analyze the flight path of the sounding rocket Libertador I, developed in 2012 at the Fundación Universitaria Los Libertadores. The main aspects that affect the motion of a rocket are propulsion and aerodynamics effects. Numerical algorithms were implemented to value the thrust provided by the rocket motor as well as aerodynamic loads. Then, the differential equations of the motion are solved using the Runge-Kutta method, RK9. Trajectory and other numerical results are calculated from a code developed in FORTRAN. Finally, graphs of the flight path, curves of the vehicle velocity as function of time are presented. Also, the algorithm permits to determine the maximum altitude and possible impact sites.